Effects of 28 Days of Oral Dimethandrolone Undecanoate in Healthy Men: A Prototype Male Pill - Thirumalai, Arthi; Ceponis, Jonas; Amory, John K; Swerdloff, Ronald; Surampudi, Vijaya; Liu, Peter Y; Bremner, William J; Harvey, Eric; Blithe, Diana L; Lee, Min S; Hull, Laura; Wang, Christina; et al. (The journal of clinical endocrinology and metabolism, 2019)
Abstract Context Dimethandrolone (DMA) has androgenic and progestational activity. Single oral doses of DMA undecanoate (DMAU) were well tolerated and reversibly suppressed serum LH and testosterone (T) in men. Objective Assess safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of oral DMAU. Design Double-blind, randomized, placebo-controlled study. Setting Two academic medical centers. Participants Healthy men (18 to 50 years). Interventions One hundred men received DMAU [0, 100, 200, or 400 mg, formulated in castor oil/benzyl benzoate (C) or powder (P)] for 28 days. Subjects underwent 24-hour PK sampling on days 1 and 28 and twice weekly ambulatory visits throughout treatment. Main Outcome Measures Primary outcomes were safety and tolerability parameters (vitals, laboratory data, mood, and sexual function scores) and adverse events. Secondary outcomes were drug PK profiles and PD effects (serum LH, FSH, and sex hormones). Results Eighty-two subjects completed the study and were included in the analysis. There were no serious adverse events. No clinically significant changes developed in safety laboratory parameters. A significant dose effect was seen for weight, hematocrit, high-density lipoprotein cholesterol, corrected QT interval, and sexual desire. Serum 24-hour average concentrations of DMAU and DMA showed dose-related increases (P < 0.001). All six subjects in the P400 group and 12 of 13 subjects in the C400 group achieved marked suppression of LH and FSH (<1.0 IU/L) and serum T (<50 ng/dL). Conclusions Daily oral administration of DMAU for 28 days in healthy men is well tolerated. Doses of ≥200 mg markedly suppress serum T, LH, and FSH. These results support further testing of DMAU as a male contraceptive. Healthy men were administered oral DMAU daily for 28 days. DMAU was safe and markedly suppressed LH, FSH, and testosterone. DMAU holds promise as a male contraceptive.